Exploring Learning Patterns Student in the Digital Age Approach Qualitative in Pancasila Education Lessons - Darmastuti, Nanda Lukitaning; Patmisari, P (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study is to know the learning patterns of students in the digital era in Pancasila Education lessons at Muhammadiyah Vocational School Sukoharjo. Methodology: Research This use method qualitative with approach descriptive done in a way gradu-ally starting from determining topic, collecting data, analyzing data, up to getting understanding material related to a Topic certain. Source data study This is head school, teacher Education Pancasila, and students. Research da-ta This is related with pattern Study students in the digital era learning Education Pancasila. Research This uses technique data collection in the form of observation, interviews, and documentation to all the parties that become the data source in study this, while for data analysis using interactive data analysis. Research conducted at Muhammadiyah 1 Vocational School, Su-koharjo (SMK Muhammadiyah 1 Sukoharjo). Results: The study reveals that students in the digital era tend to prefer group learning patterns, as it enhances their motivation, engagement, and comprehension of the learning material. An effective strategy in this context is the integration of attractive media and the use of e-learning platforms, which support the delivery of Pancasila Education. However, several challenges were identified in teaching Pancasila Education in the digital age, such as the rapid change in information, shifting student interest, and the ease of technological misuse. Applications/Originality/Value: This research provides a deeper understanding of how digital technology has transformed the way students access, process, and apply Pancasila values in their education. It offers important contributions to the development of more advanced, relevant, and effective learning models suited to the digital era. The findings can guide educators in designing appropriate teaching strategies that align with the digital behaviors of students, particularly in civic and moral education like Pancasila.